Continuity and Transformation: Álvaro Siza in Leça da Palmeira (1960s) - Pinto, P. (Final Conference_SizaAtlas. Filling the gaps for World Heritage Faculdade de Arquitetura da Universidade do Porto, 12 de setembro de 2024, 2024)
Álvaro Siza’s connection with Leça da Palmeira started with the Boa Nova Tea House (1958‒1963) and the Leça Ocean Swimming Pools (1961‒1966). The relation continued during the 1960s with two other projects: the renovation of the Leça seafront (1965‒1974 ) and the monument to the poet António Nobre (1967-1984). Siza would later return to these works, recovering the first two and partially resuming the latter ones. The place would change profoundly throughout period, sometimes in a destructive manner, which had been anticipated and countered in Siza´s proposals of the 1960s, which, as we shall see, included solutions that simultaneously brought continuity and transformation to the site’s qualities.